IMPACTO DEL RUIDO LABORAL EN LA PRODUCTIVIDAD DE LOS TRABAJADORES EN UNA EMPRESA INDUSTRIAL EN LA CIUDAD DE QUEVEDO - MURILLO DELGADO, DAGMAR NAYELHI (2025)
The present research aimed to evaluate the impact of occupational noise on the productivity of workers in an industrial company in the city of Quevedo